Content mastery services with contextual teaching and learning approaches to improve student self regulated learning - Asri Subtikasari; Neviyarni Neviyarni (Universitas Negeri Padang, 2019)
Self regulated learning in the learning process is very necessary. Students are expected to have high self-regulation so that they can be prescribed. In fact, self-regulated learning is still low, efforts are needed to improve student self-regulated learning. So there needs to be an effort to improve student self-regulated learning. Many things can be done to improve student self-regulated learning by using counseling and guidance services. This study aims to examine the differences in self-regulated learning students before and after being given treatment of content mastery services with the approach of contextual teaching and learning. This study used a pre-experimental type approach using the one group pretest-posttest design. Samples in this study were students of SMPNegeri 7 Padang class VIII 7. Data collection used questionnaires and analyzed using the Wilcoxon Signed Rank test formula. Based on the results of the study it was found that content mastery services with an effective contextual teaching and learning approach to improve student self-regulated learning.